Harnessing the Biology of Canine Intestinal Organoids to Heighten Understanding of Inflammatory Bowel Disease Pathogenesis and Accelerate Drug Discovery: A One Health Approach - Kopper, Jamie J.; Iennarella-Servantez, Chelsea; Jergens, Albert E.; Sahoo, Dipak K.; Guillot, Emilie; Bourgois-Mochel, Agnes; Martinez, Marilyn N.; Allenspach, Karin; Mochel, Jonathan P. (Frontiers in Toxicology, 2021)
In a recent issue of the Lancet, the prevalence of Inflammatory Bowel Disease (IBD) was estimated at 7 million worldwide. Overall, the burden of IBD is rising globally, with direct and indirect healthcare costs ranging between $14.6 and $31.6 billion in the U.S. alone in 2014. There is currently no cure for IBD, and up to 40% of patients do not respond to medical therapy. Although the exact determinants of the disease pathophysiology remain unknown, the prevailing hypothesis involves complex interplay among host genetics, the intestinal microenvironment (primarily bacteria and dietary constituents), and the mucosal immune system. Importantly, multiple chronic diseases leading to high morbidity and mortality in modern western societies, including type II diabetes, IBD and colorectal cancer, have epidemiologically been linked to the consumption of high-calorie, low-fiber, high monosaccharide, and high-fat diets (HFD). More specifically, data from our laboratory and others have shown that repeated consumption of HFD triggers dysbiotic changes of the gut microbiome concomitant with a state of chronic intestinal inflammation and increased intestinal permeability. However, progress in our understanding of the effect of dietary interventions on IBD pathogenesis has been hampered by a lack of relevant animal models. Additionally, current in vitro cell culture systems are unable to emulate the in vivo interplay between the gut microbiome and the intestinal epithelium in a realistic and translatable way. There remains, therefore, a critical need to develop translatable in vitro and in vivo models that faithfully recapitulate human gut-specific physiological functions to facilitate detailed mechanistic studies on the impact of dietary interventions on gut homeostasis. While the study of murine models has been pivotal in advancing genetic and cellular discoveries, these animal systems often lack key clinical signs and temporal pathological changes representative of IBD. Specifically, some limitations of the mouse model are associated with the use of genetic knockouts to induce immune deficiency and disease. This is vastly different from the natural course of IBD developing in immunologically competent hosts, as is the case in humans and dogs. Noteworthily, abundant literature suggests that canine and human IBD share common clinical and molecular features, such that preclinical studies in dogs with naturally occurring IBD present an opportunity to further our understanding on disease pathogenesis and streamline the development of new therapeutic strategies. Using a stepwise approach, in vitro mechanistic studies investigating the contribution of dietary interventions to chronic intestinal inflammation and “gut leakiness” could be performed in intestinal organoids and organoid derived monolayers. The biologic potential of organoids stems from the method’s ability to harness hard-wired cellular programming such that the complexity of the disease background can be reflected more accurately. Likewise, the effect of therapeutic drug candidates could be evaluated in organoids prior to longitudinal studies in dog and human patients with IBD. In this review, we will discuss the value (and limitations) of intestinal organoids derived from a spontaneous animal disease model of IBD (i.e., the dog), and how it can heighten understanding of the interplay between dietary interventions, the gut microbiota and intestinal inflammation. We will also review how intestinal organoids could be used to streamline the preclinical development of therapeutic drug candidates for IBD patients and their best four-legged friends.